The Role of ICMI’s West Java Regional Branch in Empowering the Community Through Economic Programs (2012–2022) - FIKY ARISTA; Rhoma Dwi Aria Yuliantri (UIN Sunan Gunung Djati Bandung, 2026)
The Indonesian Muslim Intellectuals Association (ICMI) is an organization that was established in response to the needs of intellectuals during the New Order era. The organization aims to strengthen faith and piety (Imtaq) as well as science and technology (IPTEK) as the foundation for building a civil society. Therefore, to reach various regions, Regional Organizations (Orwil), District Organizations (Orda), and Unit Organizations (Orsat) were established. Through historical research methods, this article has undergone the stages of heuristics, criticism, interpretation, and historiography. Consequently, it was found that as a fairly large regional organization, ICMI Orwil West Java plays a significant role in carrying out the tasks to fulfill the mission and objectives of the central ICMI. Thus, one of the influential aspects in its journey is the leadership’s background regarding the planned programs. ICMI West Java Regional Chapter’s programs address various aspects of society, particularly to improve human resource quality and enhance the quality of systems within political, social, and economic processes. Empowering the community through the economy demonstrates the synergy and commitment between ICMI West Java Regional Branch, ICMI Central, and autonomous bodies to collaborate with one another in fostering community self-reliance through various trainings, seminars, cooperatives, or by serving as partners and facilitators for the community.